The subcondylar osteotomy: The practical application of a novel approach - Rebecca Courtney; Eamonn Donohoe; Tom Barry (Elsevier, 2021)
The parapharyngeal space occupies an inverted pyramidal area which begins at the base of the skull and ends with its apex at the hyoid bone. Access to this area is technically challenging due to the proximity of adjacent vital structures. A variety of surgical approaches are available. The technique chosen should be dependent on the size and location of the mass to be removed. The single subcondylar osteotomy approach to the parapharyngeal space was first described by Bianci et al. Since then, there have been no further publications in the literature demonstrating the use of this technique. The following case describes the use of a single subcondylar osteotomy to access and remove a pleomorphic adenoma of the left parapharyngeal space.